Ground state solutions for a class of generalized quasilinear Schrödinger–Poisson systems - Liejun Shen (Boundary Value Problems, 2018)
Abstract This paper is concerned with the existence of ground state solutions for a class of generalized quasilinear Schrödinger–Poisson systems in R3 $\mathbb {R}^{3}$ which have appeared in plasma physics, as well as in the description of high-power ultrashort lasers in matter. By employing a change of variables, the generalized quasilinear systems are reduced to a semilinear one, whose associated functionals are well defined in the usual Sobolev space and satisfy the mountain-pass geometric. Finally, we use Ekeland’s variational principle and the mountain-pass theorem to obtain the ground state solutions for the given problem.